PTU-072 Outcomes Of The Use Of Infliximab And Adalimumab In Patients With Crohn's Disease At A District General Hospital. (9th June 2014) - Lane, C; Ramakrishnan, S; Dougherty, J
Abstract : Introduction: Infliximab (IFX) and adalimumab (ADA) are licensed for the treatment of severe Crohn's disease (CD). NICE recommends patients should receive these agents as a planned course of treatment for 12 months or until treatment failure. Patients should have their disease reassessed to determine if they have active disease and whether ongoing therapy is appropriate. We assessed our adherence to the NICE recommendations and present our outcomes for patients who had treatment discontinued following remission. Methods: Patients who had received treatment with IFX and/or ADA from Jan 2011 to Sep 2013 were identified from a database held by our pharmacy. Data was collected from patient case notes and a database of clinic letters. A total of 49 patients were identified. Cases were assessed for adherence to NICE recommendations. Results: 24 patients had been on IFX only (49%), 14 patients on ADA only (28.6%) and 11 started on IFX then switched to ADA (22.4%). 8 patients had evidence of fistulating disease. Mean age was 39 years (range 17–60). All patients (100%) had severe active CD that did not respond to conventional therapy (79.6%) or were intolerant or had contraindications (20.4%) to therapy. All patients (100%) were reassessed to determine whether ongoing treatment was still clinically appropriate. All patients (100%) were treated and reviewed by clinicians with experience in their use. Discussion regarding risks and benefits of continued treatment occurred in 77.8% of cases. 39 patients (79.6%) had been on treatment for greater than 1 year. Of these, 20 patients had treatment discontinued (51.3%); 3 were due to a reaction/intolerance, 10 were due to treatment failure, and 7 due to deep clinical remission (17.9%). 2 patients (28.6%) had disease recurrence following treatment withdrawal due to remission. Mean time to relapse following withdrawal was 9 months (range 3–15). Of all patients found to be in deep clinical remission (n = 12, 30.8%) after 12 months of treatment, 6 patients had treatment continued partly due to patient choice (66.7%). Patients who continue treatment all had their disease reassessed at least every 12 months. Conclusion: There is good adherence to NICE guidelines in our cohort, however despite evidence of deep clinical remission some patients declined to have treatment discontinued partly due to anxiety of relapse. Our relapse rate following withdrawal of biological treatment appears lower than that found in the literature. References: NICE Technology Appraisal Guidance 187: infliximab (review) and adalimumab for the treatment of Crohn's disease Louis E, et al . Maintenance of remission among patients with Crohn's disease on antimetabolite therapy after infliximab therapy is stopped. Gastroenterology 2012;142:63–70 Disclosure of Interest: None Declared.